2001
DOI: 10.1136/thorax.56.6.477
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and indoor environment in Nepal

Abstract: Background-The development of asthma seems to be influenced by the adoption of a Western lifestyle. A study was undertaken to assess the importance of indoor environmental factors in Nepal where the lifestyle and home environment diVer from that in the West. Methods-The home environment of 121 schoolchildren with asthma and 126 controls aged 11-17 years was studied. The homes of all participants were investigated and the children and their mothers were interviewed using a standardised questionnaire. Cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 32 publications
3
46
0
1
Order By: Relevance
“…Few other studies have reported similar findings. A study from Nepal of people aged 11-17 years (Melsom et al, 2001) found an adjusted odds ratio of 2.3 (1.2-4.8) for asthma among those cooking on open fires compared to wood stoves with a flue, gas, or kerosene stoves. In a large study from Nepal (N73000) adjusted odds ratios of up to six were found for some of the asthma symptoms when comparing households using only gas for cooking to only open fires (Schei et al, 2004).…”
Section: Biomass-smoke Exposurementioning
confidence: 99%
“…Few other studies have reported similar findings. A study from Nepal of people aged 11-17 years (Melsom et al, 2001) found an adjusted odds ratio of 2.3 (1.2-4.8) for asthma among those cooking on open fires compared to wood stoves with a flue, gas, or kerosene stoves. In a large study from Nepal (N73000) adjusted odds ratios of up to six were found for some of the asthma symptoms when comparing households using only gas for cooking to only open fires (Schei et al, 2004).…”
Section: Biomass-smoke Exposurementioning
confidence: 99%
“…Although evidence from developing countries suggests that IAP may increase risk of developing asthma for children, a number of studies reported no effect for children (8,(21)(22)(23)(24)(25).…”
Section: Iap Has Been Considered a Risk Factor For Copd By The Globalmentioning
confidence: 99%
“…A case-control study in Nepal assessed the home environment of schoolchildren in relation to asthma, using the International Study of Asthma and Allergies in Childhood questionnaire, and found that passive smoking and use of biomass fuels was separately associated with an increased risk of asthma in males only, but keeping animals in the home was associated with a lower risk of asthma (OR 0.2, 95% CI 0.1-0.5) [97]. This finding is supported by a similar case-control study from Kenya [95], which found that dampness in the child's sleeping area, indoor air pollution and presence of rugs or carpets in the child's bedroom were strongly associated with asthma (OR 2.0-4.9), and by a study from Guatemala in relation to asthma symptoms in 4-6-yr-old children [89].…”
Section: Series: Air Pollution and Lung Disease Op Kurmi Et Almentioning
confidence: 99%